Clinicopathologic findings and treatment outcome of laryngectomized patients with laryngeal cancer and hypopharyngeal cancer: An experience in Thailand - Noppadol Larbcharoensub (2018)
Objective: To evaluate the clinicopathologic findings and treatment outcome in laryngectomized patients with laryngeal cancer and hypopharyngeal cancer. Materials and Methods: The authors retrospectively reviewed the medical records of 212 patients who had been newly diagnosed and treated with laryngectomy between January 2000 and December 2010. The age, gender, clinical manifestations, associated predisposing condition, tumor WHO grade, AJCC tumor stage, maximum tumor size, anatomical involvement, type of surgery, postoperative sequelae, treatment and therapeutic outcome were analyzed. Results: The present study included laryngeal cancer (n = 155) and hypopharyngeal cancer (n = 57). The patients' age ranged from 38 to 84 years, with the mean age of 62.08±9.67 years. The common clinical presentations were hoarseness (73.6%), cervical lymphadenopathy (35.8%), sorethroat (22.2%), and odynophagia (14.6%). The laryngeal cancer commonly involves true vocal cord (86.5%), anterior commissure (65.8%), false vocal cord (56.8%), laryngeal ventricle (53.5%), subglottis (47.1%), and paraglotic space (35.5%), respectively. Fifty-three percent of cases had stage IV cancer. The most common postoperative surgical sequela was hypothyroidism (77.8%). The overall 5-year survivals for laryngeal cancer and hypopharyngeal cancer were 55% and 9%, respectively. The 5-year survival for node-negative cases was 61.8% versus 17% for node-positive cases (p < 0.001). AJCC stage of laryngeal cancer and hypopharyngeal cancer was a significant predictor of 5-year survival (p < 0.001 and p = 0.004, respectively). Conclusions: The advanced AJCC stage, advanced T stage, advanced N stage, extracapsular tumor spread, and tumor invasion of false vocal cord, epiglottis, preepiglottic space, paraglottic space, thyroid cartilage, cricothyroid membrane were found to significantly augment the decrease of 5-year survival in laryngeal cancer. Only advanced AJCC stage was significantly associated with 5-year survival rate in hypopharyngeal cancer.